STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMPN 02 SINGOSARI - Fanny Maulida Kurniawati; Anwar Sa’dullah; Syamsu Madyan (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Education is a must in today's era because with good education, a good generation can be created and can promise for the Nation and State. However, it also needs to be understood if good education depends on how a teacher applies their learning system in addressing these lessons and how a teacher increases student motivation to be more active and diligent in following learning especially for Islamic Religious Education (PAI) subjects. In this study, researchers applied a qualitative approach, by observing, interviewing and documenting at SMPN 02 Singoari, to find out the learning methods applied there. From the results of research conducted in January 2020, there were some data exposures, including, 1) The learning motivation in SMPN 02 Singosari has changed very well and is much better. 2) Interactive strategies using the Snowball Throwing method at SMPN 02 Singosari including, Giving the Best Value, Giving Prizes, Giving Praise, Conducting Competitions, Using Variative Methods, Providing Constructive Punishment, Utilizing the Surrounding Environment and Infrastructure Facilities. 3) From the explanation above it can be explained that in increasing motivation to learn specifically Islamic religious education there are several inhibiting factors such as, peers, teachers, facilities, infrastructure, and student conditions. Keywords: Strategy, Motivation, Qualitative, Islamic Religious Education